1973
DOI: 10.1017/s0022172400046611
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage restriction in Salmonella typhimurium by R factors and transfer factors

Abstract: SUMMARYA total of 2716 R factors and transfer factors isolated from Escherichia coli and salmonellas of human and animal origin were studied for their phage-restrictive effects in Salmonella typhimurium phage type 36. All of 1402 wild fi+ factors were non-restricting. The F factor of E. coli K12 was unique among the F-like factors tested in that it inhibited lysis of type 36 by one typing phage. In contrast, eleven distinct changes in the phage type of 36 were produced by f-I-like factors. I like plasmids can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…In animals it is the consequence of the use of antibiotics as feed additives and for the prophylaxis and treatment of disease. Moreover, it is now clear that the R factors in man and animals are drawn from a common pool (Anderson, Threlfall, Carr & Savoy, 1973;Anderson & Threlfall, 1974;Smith, Humphreys & Anderson, 1974;Anderson, Humphreys & Willshaw, in preparation).…”
Section: General Observations On the Distribution Of R Factorsmentioning
confidence: 99%
“…In animals it is the consequence of the use of antibiotics as feed additives and for the prophylaxis and treatment of disease. Moreover, it is now clear that the R factors in man and animals are drawn from a common pool (Anderson, Threlfall, Carr & Savoy, 1973;Anderson & Threlfall, 1974;Smith, Humphreys & Anderson, 1974;Anderson, Humphreys & Willshaw, in preparation).…”
Section: General Observations On the Distribution Of R Factorsmentioning
confidence: 99%
“…24 We have shown already that the frequency of resistance factors for the antibiotics used in this study varied between 20 and 83% among Typhimurium strains from Iran.4 Based on these observation, we postulated that variations observed in PTs or RTs of strains of the same BPT might reflect antibiotic pressure in I~a n .~.~~ Barker et a1., 26 testing 2010 Typhimurium strains isolated from different sources over a 3-year period in Scotland, found that four major phage-type/biotype groups (epidemic strains) accounted for > 50% of their cultures. Our findings, based on combinations of BPT, PT and RT, also demonstrate that most of the Typhimurium strains isolated during 1 year in Iran belonged to a few major BPT/PT/RTs and support the claim of Andersonz7 that, in any country where conditions are favourable for the establishment of salmonellae in man and animals, relatively few clones are responsible for the majority of infections.…”
Section: Discussionmentioning
confidence: 59%
“…fi-I-like R factors and transfer factors have been divided into eleven types by their typing phage restriction in S. typhimurium (Anderson et al 1973). Further subdivision may be possible by the determination of phage restriction in S. typhi and S. paratyphi B (Anderson, 1966).…”
Section: Discussionmentioning
confidence: 99%
“…Further subdivision may be possible by the determination of phage restriction in S. typhi and S. paratyphi B (Anderson, 1966). The F factor of K12 restricts one S. typhimurium typing phage (Anderson et al 1973) and unadapted Vi-phages III, V, VI and VII of the S. typhi Vi-typing scheme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation